A political theory of Muslim democracy - Altuntaş-Çakır, Ravza (Edinburgh studies of the globalised Muslim world, 2022)
Proposes a framework of Muslim democracy that reconciles public claims made by Muslims with the normative and practical demands of democratic regimesConstructs a Muslim democracy framework, inspired by Muslim and Western multiculturalist political thoughtProvides an inclusive typology of Muslim political thought to discover essential norms for democratic thinkingProvides an inclusive typology of multiculturalism elaborating upon its capacity to reconcile democracy with religionSynthesises these theoretical concepts and values to provide interpretative tools for a comparative political of Muslim democracyProvides a scholarly construction of the notion of a political theory of Muslim democracyRavza Altuntaş-Çakır examines the ideals, institutions and processes that shape the development of a concrete Muslim-based democratic system - a form of democracy that recognises the centrality of religion in Muslim societies. Questioning the customary characterisations of Islam's compatibility with democracy, the book adopts a comparative political theory approach that initiates a dialogue between Muslim and Western political thought. It systematically studies debates concerning Muslim political thought, multiculturalism, secularism, the public sphere and constitutionalism, which enables an exploration of Muslim democracy through a political theory approach, rather than a theological one